Pravni položaj upnikov pri uveljavljanju odškodninske odgovornosti organov vodenja ali nadzora - Fatur, Andrej (Pravni letopis, 2019)
This article primarily deals with damage liability of members of management or supervisory bodies, which is fundamentally designed as an internal liability. As a general rule under ZGD-1, the creditor has the capacity to file the company`s action for damages against members of management or supervisory bodies in order to collect the claim he has towards the company. The main condition linked to this option is the inability of the company to repay its obligations towards the creditor. If bankruptcy procedure is initiated against the company, the creditor can no longer claim compensation in his own name and for his own account, but only for the account of the company as the debtor in bankruptcy. Given the number of stakeholders involved, action for damages by creditors in material reorganisation of companies are of particular interest. ZGD-1 establishes a system of direct liability for members of management or supervisory bodies of acquired/transferor companies in mergers and divisions, whereas it is not entirely clear if the damages liability regimes are balanced in relation to creditors. The concept of protection of creditors of controlled companies in actual or contractual group companies has also been improved, offering clearer answers in regard to action for damages, especially since ZGD-1 now additionally governs waiving and offsetting of claims. Special damages liability of members of management or supervisory bodies, not having the characteristics of liability for the occurrence of the company`s financial position of insolvency, but rather the nature of non-commercial liability for damages at the moment when the company becomes insolvent, is governed by ZFPPIPP. The members of management or supervisory boards are jointly and severally liable to creditors for damages incurred due to their failure to achieve full settlement in bankruptcy procedure if the bankruptcy procedure was initiated against the company and if they could be accused of a breach of an obligation that reflects unlawful conduct. In this case, the creditor would also be entitled to file action for damages in his own name, but only for the account of the company as the debtor in bankruptcy. The creditor`s role is thus reduced only to the holder of capacity to bring proceedings for the judicial enforcement of the claim, since he does not hold any substantive rights in this regard. With this, the principle of equal treatment of creditors is consistently respected, while the current legislation also allows the creditors to seek damages when the amount of damages is not yet fully known. The right of recourse of a member of management or supervisory board is also governed by law in order for him to claim back what has been overpaid in the bankruptcy procedure.
Keywords: civilno pravo; direktorji; gospodarske družbe; nadzorni organi; odškodninska odgovornost